Determination of potassium and sodium in an ash sample by gamma-ray spectroscopy - Yamashita, Marcelo Takeshi [UNESP]; Almeida, F.; Barreiros, Ricardo Marques [UNESP]; Bringas, F.; Goldman, I. D.; Madi, T.; Pascholati, P. R.; Yamaji, F. M. (Springer, 2006)
Neutron activation analysis and gamma-ray spectroscopy were used to determine the quantity of potassium and sodium in an ash sample of Tabebuia sp bombarded with thermal neutrons. These techniques, widely applied in nuclear physics, can be used in the context of wood science as an alternative for the usual physical chemistry methods applied in this area. The quantity of K and Na in an 8.60 +/- 0.10 mg of ash was determined as being 1.3 +/- 0.3 mg and 11.0 +/- 1.8 mu g, respectively. The ratio of Tabebuia sp converted into ash was also determined as 0.758 +/- 0.004%.